First Report of Fusarium annulatum Causing Bulb Rot Disease of Tulip - Quanhong Liu; Shu Miura; Tianlan Liao; Jinyan Luo; Ying Shen; Lei Chen; Chengkai Li; Bin Li; Qianli An (Horticulturae)
Bulb rot is one of the most destructive diseases of tulip (Tulipa gesneriana L.). In November 2022, rotten tulip bulbs and terminal buds were found in Songjiang District, Shanghai, China. Fungal isolates were isolated from the rotten bulbs and identified as Fusarium based on colony morphology and ITS sequences. Further analyses of tef1, rpb1, and rpb2 barcoding sequences and conidial micromorphology identified the Fusarium isolates as F. annulatum. The pathogenicity of the F. annulatum isolates was verified with Koch’s postulates. This is the first report of F. annulatum causing bulb rot disease of tulip.